Integrating Sustainability Index Into Local Road Construction: A Strategic Approach to Sustainable Construction Management - Handayani, Fajar Sri; Sangadji, Senot (Civil Engineering Journal, 2026)
The sustainability of local road construction projects plays a critical role in the achievement of long-term environmental, social, and economic development goals. This study aimed to assess the sustainability level of local road construction projects using a structured sustainability index. The research employed a mixed-methods approach, combining a comprehensive literature review, stakeholder engagement, and the Delphi technique to determine relevant sustainability indicators and assign appropriate weightings. The sustainability index was tested and validated by means of an expert evaluation and pilot application in selected local road projects. The findings indicate that environmental aspects tend to receive higher priority compared to social and economic aspects, mainly due to the increasing global emphasis on climate change and resource conservation. However, the study also highlights the importance of integrating social equity and local economic benefits to achieve a balanced sustainable development. The novelty of this research lies in its structured index framework tailored specifically for local road projects, supported by multi-stakeholder consensus, and its potential application in infrastructure planning and public procurement processes. This study contributes to the limited body of knowledge regarding sustainability assessments in local infrastructure development, especially in developing regions. The developed index offers a practical tool for local governments and stakeholders to incorporate sustainability principles into decision-making processes.